Answer:
x<5
Step-by-step explanation:
the greater sign will firstly be changed to = for better solving so we obtain
3+9x=4(x+7)by opening bracket
3+9x=4x+28
9x-4x=28-3
5x=25
divide all through by 5x
we obtain
x=5
the greater sign change here
which is x<5
Answer:
7 students
Step-by-step explanation:
1+2+4=7students
Separate the root expression into the two numbers you found as factors, with each number now under its own square root symbol. For example, sqrt(12) = sqrt(4) times sqrt(3). 3) Keep simplifying. The square root of a perfect square becomes just a number, without theradical<span> square root symbol.</span>
Answer:
Step-by-step explanation:
4ox-16=4[10x-4]this is because 4 is the common factor in both 40and 16
16x-24x-4±12=4[4x-6x-1±3]
-8x-8=8[-1-1]